2021
DOI: 10.1177/01945998211060699
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Otolaryngology Diseases in an Urban Homeless Population

Abstract: Objective Otolaryngology diseases are common among people experiencing homelessness; however, they are seldom evaluated in a specialist setting, and investigations on their prevalence have rarely been conducted. The aim of this retrospective study was to evaluate the prevalence of otolaryngology conditions in an urban homeless population. Study Design Retrospective study. Setting Primary health care facility. Methods The clinical records of patients referred to the medical facilities of the Primary Care Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…Among included studies, there were: 5 retrospective, 4 prospective, 1 descriptive analysis, 1 cross-sectional, and 1 case-control study (Supplemental Appendix B, available online). 13,14,[16][17][18]23,24,[29][30][31][32][33] Studies were published between 1998 and 2022. Studies reported on different otolaryngology needs within different subspecialties: general OHNS (16.7%, n = 2/12), otology (66.7%, n = 8/12), pediatrics (16.7%, n = 2/12), laryngology (25.0%, n = 3/ 12), head and neck (50.0%, n = 6/12), and rhinology (33.3%, n = 4/12).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among included studies, there were: 5 retrospective, 4 prospective, 1 descriptive analysis, 1 cross-sectional, and 1 case-control study (Supplemental Appendix B, available online). 13,14,[16][17][18]23,24,[29][30][31][32][33] Studies were published between 1998 and 2022. Studies reported on different otolaryngology needs within different subspecialties: general OHNS (16.7%, n = 2/12), otology (66.7%, n = 8/12), pediatrics (16.7%, n = 2/12), laryngology (25.0%, n = 3/ 12), head and neck (50.0%, n = 6/12), and rhinology (33.3%, n = 4/12).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Two studies reported on conditions related to general OHNS. 17,23 Gurgel et al 23 examined the prevalence of head and neck diseases in an urban homeless clinic in Utah and found that 15.2% (n = 8959/59,060) of all clinic visits were accounted for by OHNS diagnoses. Upper respiratory tract infections (URTI) accounted for the greatest proportion of OHNS diagnoses, which included nasopharyngitis, tonsillitis, acute sinusitis, and laryngitis (36%, n = 3208/11,690).…”
Section: General Ohnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for basic otolaryngology care is particularly evident in vulnerable and marginalized groups, such as the diverse urban homeless population in Vatican City, which includes individuals from over 60 countries. 4 Hearing-related services for children, a particularly vulnerable group, face multiple challenges and barriers in providing access to these much-needed services. 5 Disparities in otolaryngology care outcomes are also seen in rural communities, especially related to head and neck cancers.…”
mentioning
confidence: 99%
“…Disparities in access to general otolaryngology services—especially specialized care for head and neck cancers, hearing disorders, nasal and sinus diseases, and other disorders of the ears, nose, and throat—continue to persist nationally and internationally. The need for basic otolaryngology care is particularly evident in vulnerable and marginalized groups, such as the diverse urban homeless population in Vatican City, which includes individuals from over 60 countries 4 . Hearing‐related services for children, a particularly vulnerable group, face multiple challenges and barriers in providing access to these much‐needed services 5 .…”
mentioning
confidence: 99%